2020
DOI: 10.1093/gbe/evaa191
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression Clusters and Allele-Specific Expression in Metabolism-Based Herbicide Resistance

Abstract: In the last decade, Amaranthus tuberculatus has evolved resistance to 2,4-dichlorophenoxyacetic acid (2,4-D) and 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors in multiple states across the midwestern US. Two populations resistant to both mode-of-action groups, one from Nebraska (NEB) and one from Illinois (CHR), were studied using an RNA-seq approach on F2 mapping populations to identify the genes responsible for resistance. Using both an A. tuberculatus transcriptome assembly and a high-quality grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…As P450s normally cluster together on the same chromosome in plants (Nelson and Werck‐Reichhart, 2011; Liu et al , 2016), the existence of co‐regulated gene clusters involving different types of genes (such as P450s, GSTs and UGTs) in a metabolic pathway might occur, so that CYP72A71v1 could be potentially linked to these genes conferring herbicide resistance. Co‐ordinately regulated genes clusters have been reported for biosynthesis of allelochemicals such as DIMBOA and momilactone (see a recent paper by Batada et al ., 2007; Giacomini et al ., 2020; Mao et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As P450s normally cluster together on the same chromosome in plants (Nelson and Werck‐Reichhart, 2011; Liu et al , 2016), the existence of co‐regulated gene clusters involving different types of genes (such as P450s, GSTs and UGTs) in a metabolic pathway might occur, so that CYP72A71v1 could be potentially linked to these genes conferring herbicide resistance. Co‐ordinately regulated genes clusters have been reported for biosynthesis of allelochemicals such as DIMBOA and momilactone (see a recent paper by Batada et al ., 2007; Giacomini et al ., 2020; Mao et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, modification of transcription factors allows for trans-acting modulation of gene expression. Therefore, we suggest that the differential regulation observed by Giacomini et al is the result of regulation by distal factors 23 . In a different population, Kohlhase et al identified Scaffold 15 as enriched for SNP associated with HPPD-inhibitor resistance in A. tuberculatus 15 .…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, we suggest that the differential regulation observed by Giacomini et al . is the result of regulation by distal factors 23 . In a different population, Kohlhase et al .…”
Section: Discussionmentioning
confidence: 99%
“…Plants were grown to the 12‐leaf stage in the greenhouse, whereupon apical meristems were removed to promote branching. Clones were propagated from branches 23 and grown to approximately 15 cm in height in the growth chamber to dissuade flowering. Two clones from each of 16 and 12 plants from the NEB and WUS populations, respectively, were screened for their responses to the herbicide tembotrione (Laudis, Bayer Crop Science).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation